2019
DOI: 10.1002/jlb.2mr1018-413r
|View full text |Cite
|
Sign up to set email alerts
|

Viral CD229 (Ly9) homologs as new manipulators of host immunity

Abstract: The signaling lymphocytic activation molecule family (SLAMF) of receptors plays crucial roles during innate and adaptive immune responses. The SLAMF member CD229 (Ly9, SLAMF3) is a homophilic receptor predominantly expressed on the surface of B and T cells. CD229 acts as a cosignaling molecule, regulating lymphocyte homoeostasis and activation. To promote viral replication and survival in their hosts, viruses have developed sophisticated mechanisms to combat and avoid immune surveillance. Many of these strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
(132 reference statements)
0
7
0
Order By: Relevance
“…Among these, PLAC8 were found to regulate autophagy-related functions in a variety of cancers [ 51 , 52 ]. In addition, numerous DEGs were reported to be involved in the proliferation and differentiation of immune cells and could regulate immune functions, including CD226 , IRF4 , LY9 , MS4A1 , TBX21 , TNFRSF17 , FCRLA , and SLAMF6 [ 45 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, PLAC8 were found to regulate autophagy-related functions in a variety of cancers [ 51 , 52 ]. In addition, numerous DEGs were reported to be involved in the proliferation and differentiation of immune cells and could regulate immune functions, including CD226 , IRF4 , LY9 , MS4A1 , TBX21 , TNFRSF17 , FCRLA , and SLAMF6 [ 45 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, PCED1B-AS1 could inhibit tumor cell death by cooperating with the miR-194-5p/PCED1B axis in glioma [ 93 ], and MIR4435-2HG could regulate cancer proliferation through sponging miR-206 , miR-802 , miR-128-3 and miR-1224-5p and regulated YAP1 , FLOT2 , et al, in various cancers [ 73 , 94 , 95 , 96 ]. Among all these DEGs, nearly half (24/56) have been reported to be involved in activation and differentiation of immune cells or regulation of the immune response [ 45 , 53 , 54 , 55 , 56 , 57 , 58 ]. One of them, placenta associated 8 ( PLAC8 ), has been reported to regulate autophagy by suppressing the production of IL-18, which is a pro-inflammatory cytokine that is capable of stimulating interferon gamma production and of regulating T helper cell responses [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these regulators, BZW1 is a transcription factor related to the regulation of cell cycle and proliferation [ 30 ]. LY9 was a member of SLAM family of immunomodulatory receptors [ 31 ] and interacted with the adaptor molecule signaling lymphocyte activation molecule-associated proteins. A previous study showed LY9 was related to the cancer progression and correlated to overall survival of the patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The signaling lymphocytic activation molecule (SLAM) family is a member of the CD2 protein family and is differentially expressed on the surface of immune cells 10 . Recent studies have indicated that signaling lymphocytic activation molecule family member (SLAMF) is involved in regulating adaptive and innate immune responses [11][12][13] . SLAMF7 signaling reprograms T cells toward exhaustion in the tumor microenvironment [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%